Evidence of pseudohermaphroditism in the tradition «The seven hairs of the devil» and its evolution in medical terminology in Peruvian society - Gamarra Grandez, Brian Orlando (2023)
This article will analyse the multidirectional and reciprocal influence between medicine and society, at a linguistic (terminological) level, which gave rise to the current classification and principles regarding hermaphroditism. It is based on the evidence of pseudohermaphroditism and its perception in the tradition «The seven hairs of the devil». In addition, the consequent transformation of the perception of the hermaphrodite patient will be evaluated; and thus also the change in their treatment as well as in the medical interventions that vary depending on the relationship between the patient’s selfperception and the limits set by the World Health Organisation will be evaluated. Finally, a brief review will be made of the current state of the art of the basic criteria of the doctorpatient relationship when treating a person with this condition.